Detection and genetic identification of pestiviruses in Brazilian lots of fetal bovine serum collected from 2006 to 2014 - Francielle L. Monteiro; Juliana F. Cargnelutti; Patrícia Braunig; Aurea V. Folgueras-Flatschart; Nathália C. Santos; Edviges M. Pituco; Rudi Weiblen; Eduardo F. Flores (Pesquisa Veterinária Brasileira)
ABSTRACT: The present study performed a genetic identification of pestiviruses contaminating batches of fetal bovine serum (FBS) produced in Brazil from 2006 to 2014. Seventy-three FBS lots were screened by a RT-PCR targeting the 5’untranslated region (UTR) of the pestivirus genome. Thirty-nine lots (53.4%) were positive for pestivirus RNA and one contained infectious virus. Nucleotide sequencing and phylogenetic analysis of the 5’UTR revealed 34 lots (46.6%) containing RNA of bovine viral diarrhea virus type 1 (BVDV-1), being 23 BVDV-1a (5’ UTR identity 90.8-98.7%), eight BVDV-1b (93.9-96.7%) and three BVDV-1d (96.2- 97.6%). Six lots (8.2%) contained BVDV-2 (90.3-100% UTR identity) being two BVDV-2a; three BVDV-2b and one undetermined. Four FBS batches (5.5%) were found contaminated with HoBi-like virus (98.3 to 100%). Five batches (6.8%) contained more than one pestivirus. The high frequency of contamination of FBS with pestivirus RNA reinforce the need for systematic and updated guidelines for monitoring this product to reduce the risk of contamination of biologicals and introduction of contaminating agents into free areas.